Armenia International Outmigration : An Exploration on the Effects on Armenian Households’ Welfare - World Bank (World Bank, Washington, DC, 2019)
This report analyzes issues related to international migration in Armenia and its impact on Armenian households’ welfare. The report uses microdata coming from two recent household surveys, the 2017 Russian-Armenian University survey, a nationally-representative household focused on international migrants and their origin households, and the 2017 Integrated Living Conditions Survey, nationally representative household conducted by the Statistical Committee focused on welfare measurement but also with information on international migrants. The report finds that among international migrants, there are some slight differences in the profile of permanent and temporary migrants. Permanent migrants tend to be younger, more educated and are more likely to come from secondary cities, in contrast to temporary migrants, who are a bit older, less educated and are more likely to come from rural areas. Employment prospects for both groups are very limited the moment they leave the country, with employment rates around 25 percent. They tend to migrate largely to the Russian Federation, where they are hired almost exclusively by firms in the private sector. Temporary workers overwhelming work in the construction sector, while permanent workers show more diversity in sectors of employment.